Comparison of Resin Infiltrant and Sealants on Pre-Cavitated Lesions in Primary Teeth: A Quantitative Analysis Using Atomic Absorption Spectrophotometry - Shailaben Chaudhary; Shobha Fernandes; Hardikkumar B. Patel; Priya Mishra; Nishan R. Patel; Yash Bafna; Miral Mehta (Journal of Pharmacy and Bioallied Sciences)
Aim: This study was conducted to analyze the effects of sealants and resin infiltrant on pre-cavitated lesions in primary teeth (AAS) using an atomic absorption spectrophotometer. Material and Method: Forty freshly extracted intact human primary molars were used for the study. All the specimens were then divided into four groups of ten specimens. These groups are treated differently. The specimens were stored in artificial saliva throughout the study. The AAS was then used to assess the calcium dissolution of artificial saliva. Result: A comparison of Group III and Group IV established a statistically significant difference found in the amount of calcium dissolution in artificial saliva. Group III showed lesser calcium dissolution from enamel compared to Group IV in artificial saliva. Conclusion: Resin infiltration showed more resistance to the release of calcium from enamel as compared to Clinpro Sealant in artificial saliva.